PENGARUH INHIBITOR SISTEIN PADA FERMENTASI BIJI KAKAO TERHADAP KANDUNGAN POLIFENOL - Dewi Nurhayati; Yuliansyah Sundara Mulia; Amadda Fadhila Azhiima (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2022)
Obesity is a condition of excessive accumulation of fat in the body. Dietary fiber and anthocyanins have beneficial effects on obesity. The aim was to determine the effect of the product's formulation of oat flour and fermented glutinous black rice on organoleptic aspects, dietary fiber content, and anthocyanin content. This research design used an experimental study with a completely randomized design. This research method used a hedonic test on 30 panelists to determine organoleptic properties, pH differential for anthocyanin levels, and enzymatic gravimetric for dietary fiber levels. The formulation between oat flour and fermented glutinous black rice obtained was F1 (30:70), F2 (50:50), and F3 (70:30). F2 product has the best rating on all organoleptic aspects, including color, aroma, texture, taste, and overall. The results of the Kruskal Wallis test showed a significant difference in the texture aspect of the product. The anthocyanin content in the product is 5.72 mg/100 grams, and the fiber content in the product is 7.36%. It is hoped that further research will be carried out to determine the effectiveness of oat fermented glutinous black rice cookies on samples with obesity.